PENGGUNAAN GAYA MENGAJAR “MOSSTON” OLEH GURU PENDIDIKAN JASMANI DI SMA SE-KOTA YOGYAKARTA - R. Aditya Budi Setiawan, Soni Nopembri (Jurnal Pendidikan Jasmani Indonesia, 2013)
This study aims to determine the level of use of teaching styles “Mosston” the teachers of physical education in highschools in the city of Yogyakarta. This research is a descriptive study, the method used in this study is a survey methodusing instruments such as questionnaires, and the questionnaire used was a questionnaire enclosed questionnaire ispresented with four alternative answers. Subjects in this study are a physical education teacher at the high schools inthe city of Yogyakarta. Physical education teachers who participated in this study amounted to 55 people. Analysis ofthe data in this study used descriptive analysis and calculations for each item in the questionnaire using percentages.The results showed that the level of use of teaching styles “Mosston” by a physical education teacher in a sequenceis a style of command in the very high category (80.0 %), style check in the high category (65.5 %), individual stylein the high category (60.0 %), their own teaching style in the category of very high (60.0 %), the style leader in thediscovery of the high category (54.5 %), convergent force (52.7 %), the style inclusion in the category of very high(49.1 %), the task force in the high category (47.3 %), the style diverges in the high category (41.8 %) , reciprocalstyle in the medium category ( 40.0 % ) , style initiative in the high category (36.4 %). For the level of use of teachingstyles “Mosston” used by the sports and health education teacher high schools in the city of Yogyakarta is based onthe results of this study are the categories sequentially higher by 34 people (61.8 %), second best in the categoryof very high total of 11 people (20 %) ranked third in the category were as many as 10 people (18.18 %) and leastin the category of low and very low as 0 persons (0.0 %), so overall it can be concluded that the use of teachingstyles “Mosston” by a sports and health education high school teacher at the city of Yogyakarta in the high category .Keywords: Teaching Style, Usage, Sports and Health Education Teacher.